Production of alpha-amylase enzyme from grain sprouting - Saeed Khalif Salman; Ahmed Farhoud Ktub; Ali Taaman Nayef (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Alpha-amylase is considered to be one of the primary enzymes responsible for starch degradation in cereals. During grain germination, α-amylase initiates the conversion of starch into simple sugars to fuel embryo and coleoptile growth in the first few days of germination. The present study involves the estimation of Alpha amylase content in four different grains varieties, namely, wheat grain and barley up to 8 days after germination. It was observed that, alpha amylase content steadily increased, and found to be saturated after reaching the peak values. In all the samples, the peak values were observed in 7th day of germination. The enzymatic assay were done by estimation of maltose content by Spectrophotometry as starch degraded to maltose by alpha amylase enzyme.